2014
DOI: 10.1002/jbmr.2318
|View full text |Cite
|
Sign up to set email alerts
|

SDF-1/CXCR4 Axis in Tie2-Lineage Cells Including Endothelial Progenitor Cells Contributes to Bone Fracture Healing

Abstract: CXC chemokine receptor 4 (CXCR4) is a specific receptor for stromal-derived-factor 1 (SDF-1). SDF-1/CXCR4 interaction is reported to play an important role in vascular development. On the other hand, the therapeutic potential of endothelial progenitor cells (EPCs) in fracture healing has been demonstrated with mechanistic insight of vasculogenesis/angiogenesis and osteogenesis enhancement at sites of fracture. The purpose of this study was to investigate the influence of the SDF-1/CXCR4 pathway in Tie2-lineage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(57 citation statements)
references
References 49 publications
2
52
0
Order By: Relevance
“…Previous studies have shown that early deletion of the CXCR4 gene in osteoblastogenesis disrupts osteoblast formation and bone development [32]. It has been reported that SDF-1/CXCR4 signaling in the mature osteoblast can feedback to regulate the osteoclast precursor pool size and play a multifunctional role in regulating bone formation and resorption [33]. SDF-1 might induce cell migration to the injury area, which is consistent with the results of the present study.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have shown that early deletion of the CXCR4 gene in osteoblastogenesis disrupts osteoblast formation and bone development [32]. It has been reported that SDF-1/CXCR4 signaling in the mature osteoblast can feedback to regulate the osteoclast precursor pool size and play a multifunctional role in regulating bone formation and resorption [33]. SDF-1 might induce cell migration to the injury area, which is consistent with the results of the present study.…”
Section: Discussionsupporting
confidence: 92%
“…Tyrosine Kinase with Immunoglobulin-Like and EGF-like domains (Tie2)-Cre CXCR4 negative endothelial progenitor cells were shown to have reduction of migration and colony forming action in comparison to wild type cells. This effect was confirmed in vivo with delayed fracture healing and smaller callus size in Tie2-cre CXCR4 conditional knockout mice (34). AMD3100 is a CXCR4 inhibitor that induces progenitor cells to migrate to the peripheral blood due to lack of CXCR4/SDF-1 binding that anchors these progenitors in their niches.…”
Section: Accepted Manuscriptmentioning
confidence: 82%
“…Our data showed that the SDF-1α/Col/HA group had more CD34-positive cells than the Col/HA group, indicating that SDF-1α may magnify the vessel formation ability of the scaffold with optimal matrix elastic modulus. Besides, another important reason is that SDF-1α may involve in attracting of CD34-positive hematopoietic stem cells 23 and endothelial progenitor cells 45 .
Figure 7Immunofluorescent detection of CD34 in scaffolds after subcutaneous implantation. The white arrow indicates typical blood vessel.
…”
Section: Resultsmentioning
confidence: 99%